Rezonans mechaniczny przy drganiach skrętnych pręta lepkosprężystego - FORYŚ, Anna; FORYŚ, Andrzej (Engineering Transactions, 1971)
Mechanical resonance near twisted vibration in a viscoelastic rod This paper concerns the resonance phenomenon in a rod of circular diameter made of viscoelastic material without ageing. The object is to investigate the usefulness of a given theory for determination of the free intensity vibrations and resonance intensities of the rod.The upper end of the rod is fixed; at the lower end the mass of the moment of inertia is greater than the moment of inertia of the rod. On the lower end acts a sinusoidally variable moment of a force compelling twisted vibrations. The equation of vibration and its solution for a given creep function is given. In the experimental part investigations were made of the creep of a rod during twisting, vibrations of a rod, and the dependences of the amplitude vibrations at the lower part of a rod caused by the intensity of the force.In conclusion, experimental and theoretical results are compared. Agreement of these results is satisfactory.